PENGARUH SELF CONTROL DAN FINANCIAL ATTITUDE TERHADAP SAVING BEHAVIOR PENGGUNA LAYANAN BUY NOW PAY LATER - Putu Putri Prawitasari (JURNAL ILMIAH EDUNOMIKA, 2023)
The development of online loans that are increasingly in demand by the public due to digital developments leads to transactions in shopping through the marketplace with a payment scheme with the term Buy Now, Pay Later (BNPL) or commonly called pay later, as a provider of financial service facilities in the form of installment payment methods without a credit card. The pay later facility allows consumers to better manage cash flow, especially during a pandemic that is full of uncertainty, so that consumers can more freely manage to budget and plan long-term finances. This study aimed to determine the effect of self-control and finance attitude on saving behavior. This study uses a descriptive type of research with a quantitative approach that describes the behavior of respondents regarding the effect of Self Control and Finance Attitude on the Saving Behavior of users of the Atome application buy now pay later service in Denpasar Bali. Based on the research object, this study's population is the residents of Denpasar City who use the Atome Pay later Application. The method of determining the sample in this study used the Non-Probability Sampling technique with purposive sampling technique, with the number of samples determined by the Cochran formula, the minimum number of samples in this study was 97 respondents. The number of samples in this study was 117 respondents. The results showed that Self Control and Finance Attitude positively affected Saving Behavior.